2023
DOI: 10.1101/2023.04.04.535587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harmonized diffusion MRI data and white matter measures from the Adolescent Brain Cognitive Development Study

Abstract: The Adolescent Brain Cognitive Development (ABCD) study is a groundbreaking effort aimed at providing a comprehensive understanding of adolescent brain development. With data collected from over 10,000 children across 21 sites, this study promises to unlock key insights into the cognitive, behavioral, and neuroimaging data that underpins this critical period of development. However, the potential use of diffusion MRI (dMRI) data in this study is hindered by site-specific scanner and protocol variability, which… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The ABCD Study dataset provides the advantages of a largescale data set, but since it has been collected across multiple sites with site-specific scanner variability, there are challenges to using and processing the raw dMRI data. To overcome this challenge, the ABCD team has harmonized data across sites, performed the white matter parcellations, and ran the whole-brain tractography resulting in quality-controlled neuroimaging data for over 9000 of their participants (Cetin-Karayumak et al, 2023). The present study utilizes the harmonized data provided by the ABCD Study researchers to avoid potential processing issues.…”
Section: Limitationsmentioning
confidence: 99%
“…The ABCD Study dataset provides the advantages of a largescale data set, but since it has been collected across multiple sites with site-specific scanner variability, there are challenges to using and processing the raw dMRI data. To overcome this challenge, the ABCD team has harmonized data across sites, performed the white matter parcellations, and ran the whole-brain tractography resulting in quality-controlled neuroimaging data for over 9000 of their participants (Cetin-Karayumak et al, 2023). The present study utilizes the harmonized data provided by the ABCD Study researchers to avoid potential processing issues.…”
Section: Limitationsmentioning
confidence: 99%
“…To this end, the minimally processed dMRI data (3.0 release) were harmonized with our well-validated approach based on rotation invariant spherical harmonics (RISH, https://github.com/pnlbwh/dMRIharmonization; Cetin- Karayumak et al, 2019Karayumak et al, , 2020. Details on the specifics of the harmonization used in the current study are reported by Cetin- Karayumak et al (2023b). We note that diffusion data acquired on MRI scanners manufactured by Philips did not pass quality control criteria during harmonization (Cetin- Karayumak et al, 2023b), which led to the exclusion of n = 38 children with mTBI, n = 75 TDC and n = 80 OI controls from imaging analyses.…”
Section: Psychological Medicinementioning
confidence: 99%
“…Details on the specifics of the harmonization used in the current study are reported by Cetin- Karayumak et al (2023b). We note that diffusion data acquired on MRI scanners manufactured by Philips did not pass quality control criteria during harmonization (Cetin- Karayumak et al, 2023b), which led to the exclusion of n = 38 children with mTBI, n = 75 TDC and n = 80 OI controls from imaging analyses. The final sample size for dMRI analyses used in this study was n = 321 children with mTBI (n = 636 TDC, n = 656 OI).…”
Section: Psychological Medicinementioning
confidence: 99%
See 1 more Smart Citation